Addressing Health Disparities: Increasing Black Male Representation in Nursing. - Spurlock, Wanda R.; Brown, Sandra C.; Hollins, Marlin L. (ABNFF Journal, 2025)
As the nation's population becomes increasingly diverse, expanding the racial and gender composition of the nursing workforce is critical to addressing health disparities and achieving health equity. Compounding the gender disparity in the nursing workforce is the underrepresentation of African American males in nursing. The dearth of African American male nurses translates to missed opportunities to improve health outcomes in minority populations, especially African American males, whose health remains worse than nearly all other groups in the United States (Ballard, 2024). Committed to educating diverse minority populations, Historically Black Colleges and Universities (HBCUs) are a pipeline to expand the nation's minority healthcare workforce. This paper examines the critical intersection of Black men's health, health disparities, and the underrepresentation of Black male nurses in the healthcare workforce while highlighting the efforts of an HBCU nursing program in addressing these issues.